Interpreting Cost-Benefit Concept of Local Wisdom Karapan Sapi Madura : Socio-Psychological Perspective - Leniwati, Driana; Rohani, Siti; Ahmad Juanda; Agung Prasetyo NW; Fahmi Dwi Mawardi (Riset Akuntansi dan Keuangan Indonesia, 2024)
This study aims to interpret the cost-benefit concept based on a socio-psychological perspective. This research uses an interpretive paradigm with a case study research design approach. The result found that the meaning of cost-benefit is divided into two groups, namely 1) the concept of material cost-benefit based on a socio-psychological perspective, where costs are interpreted as economic sacrifices and benefits are interpreted as society's perception of dignity (social and material status), 2) the non-material cost-benefit concept based on a socio-psychological perspective where costs are interpreted as a sense of pride (prestige) and strengthening family relationships. This study contributes to theory and practice which the interpretation of the cost-benefit concept in accounting has a broader context where costs are interpreted not just material (money) but there are non-material values that are formed because of the social and psychological environment and in terms of policy in the company, this interpretation can be taken into consideration in making policies. The novelty is trying to look at the concept of cost-benefit from a different perspective from accounting science, namely from a social psychology perspective which is expected to raise human awareness for the better.